(untitled) (Fiep Bulletin - online, 2014)
Soccer is a world-known sport and, especially in Brazil, it is a synonym of identification with the local culture. Technology presents itself as a source of knowledge innovation and possibilities which aggregates values when they are, adequately, used. The purpose of this study is to demonstrate how information technology can be considered an ally to the decision-making process of sports managers in soccer clubs or associations. It is a bibliographic study that presents situations in which technological resources are used to increase the performance of athletes during their training section and competitions. These resources also come to be efficient in which the identification of problems, anticipation of solutions and athletes´ recovery are concerned. In sports events, the usage of technology contributes to the setting of a journalistic coverage as well as the safety of audience and scope of broadcastings. It also comes to be a key factor in the final result reached by the teams in some matches.